Push and pull - Freeman, Marcia S. (Marcia Sheehan), 1937- (New York : Newbridge Educational Publishing, 1997)
Simple text and photographs describe the mechanics of pushing and pulling and its applications.
Cover title.
Includes index.
Keywords: Force and energy -- Juvenile literature; Mechanics -- Juvenile literature; Force and energy; Mechanics; Oversize books